KEPEMIMPINAN KETUA MUTIARA ILMU MULIA YAYASAN BERDASARKAN KECERDASAN EMOSIONAL (EQ) DI LEMBAGA PENDIDIKAN SD IT TIARA AZ ZAHRA KOTA PALANGKA RAYA - Syarwani Abdan (UNISAN JURNAL, 2024)
This research reveals that the emotional intelligence-based leadership of the Chairman of Mutiara Ilmu Mulia Foundation has a significant impact on the motivation and well-being of students, teachers and staff at SD IT Tiara Az Zahra, Palangka Raya City. The attitude of empathy, appreciation and support shown by the Chair creates a conducive learning environment, motivates students to learn better, and improves the welfare of all school members. Students feel a positive boost in their learning motivation because of the empathy and appreciation given by the Chair. This makes them feel appreciated and motivated to achieve. Teachers also feel the positive impact of the Chair's leadership, who is able to listen and understand the problems faced by teachers, so that teachers feel supported and motivated to improve their performance. Likewise with administrative staff and employees, they also feel the positive influence of the Chairman's leadership which builds harmonious relationships. Apart from that, the Chair's leadership based on emotional intelligence also has a positive impact on increasing student academic achievement. The chairman is able to increase student learning motivation, manage conflict well, and collaborate in developing a curriculum that is relevant and enjoyable for students. To develop emotional intelligence in oneself and the surrounding environment, the Chairman of the Mutiara Ilmu Mulia Foundation can implement strategies such as increasing self-awareness, managing emotions and behavior appropriately, understanding other people's emotions, building healthy relationships, as well as holding training and workshops on intelligence emotional. Thus, it can be concluded that the leadership of the Chairman of the Mutiara Ilmu Mulia Foundation based on emotional intelligence has a positive influence on the motivation and welfare of students, teachers and staff, as well as on increasing student academic achievement at SD IT Tiara Az Zahra, Palangka Raya City. Keywords: